The role of transport in the development of the tourist activity: A bibliometric analysis [El papel del transporte en el desarrollo de la actividad turística: Un análisis bibliométrico] (2016)
The tourist activity is performed in an unusual environment implying a shift in the space. In this sense, transport meets essential functions in its development in both as a mechanism for transit and as a touristic experience. This study aims to study the evolution and trends of the publications on transport and tourism in the period 1985-2015 from a theoretical and conceptual perspective. To achieve this, a bibliometric analysis was carried out from a search equation in the Scopus database. Indicators of quantity, quality, structure and sub-areas were obtained, identifying an increase in the number of publications per year and a growth in the number of authors. Furthermore, transportation infrastructure, environmental protection and air transport are some of the sub-areas studied. © 2016, Universidad de los Andes. All rights reserved.